Increasing Cognitive Abilities Through Problem Solving-Based Learning - Mukhlisin, Miftahul; Alayubi, Muhammad Silahudin; Bintang Zein Al-Hazmi; Hayani, Aida (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2024)
Enhancing Cognitive Abilities through Problem-Solving-Based Learning: A Literature Review Education plays a crucial role in the intellectual development of students, and problem-solving-based learning methods have emerged as a promising approach. This is research is qualitative research approach with   literature review. Literature review is investigates the positive impact of problem-solving-based methods in enhancing students' cognitive abilities across various educational levels. Data analysis technique are reduction data, display data, verification and analysis. The study provides a comprehensive examination of empirical evidence highlighting the key benefits of problem-solving methods, including the development of critical thinking, problem-solving skills, and creativity. Through careful analysis, it is found that this approach has been proven to be effective in improving students' cognitive abilities. The review also encompasses several case studies illustrating successful implementations of problem-solving methods within formal educational contexts. In conclusion, this literature review offers strong evidence of the advantages of integrating problem-solving methods in education. The development of robust cognitive abilities is a vital key to assist students in meeting the demands of the future. Therefore, the findings in this review serve as a foundation supporting the development of curriculum that focuses on strengthening students' cognitive abilities.